2017
DOI: 10.1007/s00068-017-0785-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of relative centrifugal forces increases growth factor release within solid platelet-rich-fibrin (PRF)-based matrices: a proof of concept of LSCC (low speed centrifugation concept)

Abstract: Moreover, platelets were located homogenously throughout the matrix in the A-PRF and A-PRF+ groups, whereas platelets in PRF were primarily observed within the lower portion. Discussion the present results show an increase growthfactor release by decreased RCF. However, further studies must be conducted to examine the extent to which enhancing the amount and the rate of released growth factors influence wound healing and biomaterial-based tissue regeneration. Conclusion These outcomes accentuate the fact that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
152
0
15

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(174 citation statements)
references
References 38 publications
7
152
0
15
Order By: Relevance
“…PDGF and VEGF promote the chemotaxis of macrophages and can indeed favor the migration of fibroblasts. Similar results are reported by El Bagdadi et al and Masuki et al, who observed also an enhanced proliferation of human periosteal cells for the A‐PRF + stimulated cultures. Our results are in agreement with the aforementioned research groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…PDGF and VEGF promote the chemotaxis of macrophages and can indeed favor the migration of fibroblasts. Similar results are reported by El Bagdadi et al and Masuki et al, who observed also an enhanced proliferation of human periosteal cells for the A‐PRF + stimulated cultures. Our results are in agreement with the aforementioned research groups.…”
Section: Discussionsupporting
confidence: 90%
“…A more recently adapted protocol (A‐PRF+) makes use of a centrifugation step using a lower g‐force (and 33% reduced time which is also of influence). The latter protocol has been demonstrated to give a higher and more evenly distributed number of platelets throughout the fibrin matrix, but a lower number of leukocytes, although more evenly dispersed in the matrix …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various research groups have continued to misrepresent RCF values with little detail provided on the rotor sizes, rotor angulation, tube sizes and/or manufacturer of the centrifugation system and this article aims to define a guideline for future studies reporting RCF values in studies related to PRF . One of the confusions that has been created in the field over the years is that various research groups may report RCF values at the PRF clot (referred to as RCF‐clot; location at which the PRF clot is formed), whereas others have reported RCF values either at the minimum or maximum of centrifugation tubes (referred to as RCF‐min or RCF‐max). This article aims to clarify these misunderstandings and proposes that a consensus be reached regarding more accurate means to report g‐force values in future studies investigating PRF.…”
Section: Introductionmentioning
confidence: 99%
“…We have compared the mechanical and degradation properties of advanced PRF (A‐PRF) and concentrated growth factors (CGF) and found no statistically significant differences . The current main topic in the comparison of PRF is their abilities to retain and release growth factors . In some studies, an A‐PRF matrix prepared by low‐speed centrifugation has been demonstrated to be superior to a CGF matrix prepared by high‐speed centrifugation.…”
Section: Introductionmentioning
confidence: 99%